2022
DOI: 10.3390/vaccines10040556
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Booster Vaccination by CoronaVac or BNT162b2 in Previously Two-Dose Inactivated Virus Vaccinated Individuals with Negative Neutralizing Antibody

Abstract: COVID-19 has swept across the globe since 2019 and repeated waves of infection have been caused by different variants of the original SARS-CoV-2 (wild type), with the Omicron and Delta variants having dominated recently. Vaccination is among the most important measures in the absence of widespread use of antivirals for prevention of morbidity and mortality. Inactivated virus vaccine has been abundantly used in many countries as the primary two-dose regimen. We aim to study the safety and immunogenicity of Coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Risk of bias assessment of the included RCTs [ 14 , 24 , 26 , 27 , 30 , 31 , 35 , 37 , 40 , 41 , 45 ]. …”
Section: Resultsmentioning
confidence: 99%
“…According to a local serological study, T cell response was shown to be higher in two-dose-BNT162b2 recipients when compared to those who received two doses of CoronaVac [ 41 ]. Among those who received CoronaVac as the first two doses, more heterologous (BNT162b2) booster recipients developed positive T cell response than homologous booster recipients [ 42 ]. In contrast to these immunological findings, we did not demonstrate a significant difference between the risk of COVID-related mortality or complications, among those who completed three doses of CoronaVac versus BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…Using an interferon-gamma release assay, BNT126b2 booster was also found to induce a better T-cell response. [34] Our current study has provided real world data on enhanced protection against Omicron with heterologous boosting after 2 doses of CoronaVac. We showed that 3-dose vaccination significantly reduced the chance of COVID-19 and according to regression analysis, the effect mainly came from BNT162b2 booster.…”
Section: Discussionmentioning
confidence: 96%